Influence of pyrolytic and non-pyrolytic rice and castor straws on the immobilization of Pb and Cu in contaminated soil. Issue 21 (1st November 2016) - Rizwan, Muhammad Shahid; Imtiaz, Muhammad; Chhajro, Muhammad Afzal; Huang, Guoyong; Fu, Qingling; Zhu, Jun; Aziz, Omar; Hu, Hongqing
ABSTRACT: Soil contamination with heavy metals has become a global environmental health concern. In the present study, European Community Bureau of Reference (BCR) sequential extraction and toxicity characteristic leaching procedure (TCLP) techniques were used to evaluate the Pb and Cu subsequent transformations, immobilizing impact of pyrolytic and non-pyrolytic rice and castor straws and their efficiency to reduce the metals mobility and leachability in the polluted soil. Obtained results highlight the potential of biochar over non-pyrolytic residues to enhance the immobilization of Pb and Cu in the soil. Castor leaves-derived biochar (CLB), castor stem-derived biochar (CSB), and rice straw-derived biochar (RSB) prominently decreased the mobility (acid-soluble fraction) of Pb 49.8%, 31.1%, and 31.9%, respectively, while Cu decreased 15.8%, 11.5%, and 12%, respectively, as compare to control. Sequential extraction showed that biochar treatments prominently modified the proportioning of Pb and Cu from acid soluble to a less bioavailable fraction and increased the geochemical stability in the polluted soil as compared to relative feedstocks as well as the controlled soil. Additionally, the soil pH increased markedly after the addition of biochar. Compared with control, the TCLP-extractable Pb and Cu were reduced to 29.2–41.4% and 5.7–22.8% from the soil respectively by the application of CLB. The immobilization and reduction in leachability of Pb and Cu were correlated with the soil pH. The biochar effect on the Pb immobilization was much better as compared to Cu in co-contaminated soil. Overall addition of CLB offered the best results and could be effective in both Pb and Cu immobilization thereby reducing their mobility and bioavailability in the co-contaminated soil.